Epigenetic aberrations of miR-369-5p and DNMT3A control Patched1 signal pathway in cardiac fibrosis. (1st December 2018) - Tao, Hui; Dai, Chen; Ding, Ji-Fei; Yang, Jing-Jing; Ding, Xuan-Sheng; Xu, Sheng-Song; Shi, Kai-Hu
Graphical abstract: Highlights: Post-translational of epigenetic plays a key role in CFs proliferation and fibrosis. miR-369-5p targets DNMT3A control CFs activation and fibrosis. DNMT3A hypermethylation of Patched1 pathway leads to fibroblast proliferation. miR-369-5p and DNMT3A is novel therapeutic target for cardiac fibrosis. Abstract: Modulation of epigenetic marks has promised efficacy for treating fibrosis. Cardiac fibroblast is the primary source of activated myofibroblasts that produce extracellular matrix (ECM) in cardiac fibrosis, but the mechanisms underlying this process are incompletely understood. Here we show that microRNA-369-5p (miR-369-5p) through DNMT3A hypermethylation and suppression of the Patched1 pathway leads to fibroblast proliferation in cardiac fibrosis. Forty adult male Sprague-Dawley (SD) rats were randomly divided into two groups (sham and AAC group), cardiac fibrosis was produced by abdominal aortic constriction, and the operation of abdominal aortic constriction was carried out according to the method described. Cardiac fibroblasts (CFs) were harvested from SD neonate rats and cultured. Importantly, miR-369-5p bind directly to DNMT3A with high affinity. MiR-369-5p leads to inhibition of DNMT3A enzyme activity. Exogenous miR-369-5p in cells induces aberrant DNA methylation of the Patched1, resulting in hypermethylation of low to moderately methylated regions. Moreover, Overexpression of miR-369-5p in cardiac fibroblast cells inhibits proliferation. We identify DNMT3A as miR-369-5p target genes and demonstrate that inhibition of miR-369-5p expression augments cell proliferation by activating DNMT3A and suppression of the Patched1 pathway. Together, our results highlight miR-369-5p mediated DNMT3A epigenetic silencing of Patched1 as a mechanism of fibroblast proliferation in cardiac fibrosis.